Penalaran Moral Dalam Mencegah Delikuensi Remaja - Harmathilda Hasanusi (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2019)
Discussing about adolescent is never separated from social life, environment or his/her behavior. Adolescent is a person that no longer seen as a child, but can not be said as an adult as well. In this condition, sometimes they make troubles or problems. Then, there is an assumption that adolescents are a strange group because they have values ​​that are different from their parents or people who are more mature than them. So, it is very important to understand the moral reasoning by all children in preventing adolescent delinquency. Moral reasoning is how a person can make a decision whether what he does is something good or bad; the reason for them to think that whatever they do is considered good or bad. Moral reasoning develops in the order of stages. Therefore, children always need guidance from parents or teachers so they can always move carefully according to the level of reasoning.